The death of a poet : the last days of Marina Tsvetaeva - Kudrova, I V. (Overlook Duckworth, 2004)
The Death of a Poet is the harrowing narrative account of how the forces of history and fate combined to destroy the life of one of twentieth-century Russian literature's most talented and esteemed poets during the bloodiest period of Stalin's regime.